Spheres of global justice : Volume 1 Global Challenges to Liberal Democracy. Political Participation, Minorities and Migrations; Volume 2 Fair Distribution - Global Economic, Social and Intergenerational Justice - Merle, Jean-Christophe (Springer Netherlands, 2013)
Spheres of Global Justice analyzes six of the most important and controversial spheres of global justice, each concerning a specific global social good. These spheres are democratic participation, migrations, cultural minorities, economic justice, social justice, and intergenerational justice. Together they constitute two constellations dealt with, in this collection of essays by leading scholars, in two different volumes: Global Challenges to Liberal Democracy and Fair Distribution. These essays illustrate each of the spheres, delving into their differences, commonalities, collisions and interconnections. Unlike many writings on global justice, Spheres of Global Justice does not content itself with describing the painful and advantageous effects of the globalization process as being ipso facto a global injustice or a just global order. Rather, this multidisciplinary collection of essays, from a pluralist inspiration, combines empirical analysis with theoretical approaches and ethical principles, paying close attention to two aspects of the effects of the globalization process. These aspects are the causal relationships that lead to such effects and the kinds of obligations, or of normative relationships between global rights and correlative duties, that applies to each specific individual case. This volume illustrates how diverse global obligations are, and how they can be, grounded in diverse relationships (identity, ability to provide help, causal responsibility, past injustices, protection of agency and promotion of independence, etc.). These essays also demonstrate that an ethical global approach has not only international or transnational, but also domestic, local and interpersonal dimensions.